HAM dan Hukum Islam : (Tinjauan Atas Penerapan Hukum Di Masyarakat) - Yamani, Gasim (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2021)
Ham as an agreement made by humans, has legal force that is recognized by the whole world. On the other hand, Islam as a religion also has a source of law that regulates human life and of course the laws regulated in Islam are in the name of God and justice. Human rights debates often occur when Islamic law wants to be applied, for example, cutting hands, capital punishment and so on. Though the punishment is in the name of God and justice. This is the object of a research study on how Islam views human rights, this study has also been carried out by several researchers such as Sitti Aminah's writing with the title "Human Rights in the Perspective of the Qur'an", besides that there is an article from Nur Asiah who wrote an article with the title Rights Human Rights Perspective of Islamic Law. Although these two articles write about human rights, there is a difference with this research, which lies in the methodology and discussion. The methodology used is the comparative method, which means that comparisons between several cases of Islamic law and ordinary legal cases such as imprisonment and hand cutting are compared. The conclusion from the results of this study or this paper is that human rights and Islamic law both want to create justice, only that the difference between the source of the decision is if human rights are in the name of human justice while Islamic law is in the name of God and justice.